2012
DOI: 10.4244/eijv8i1a13
|View full text |Cite
|
Sign up to set email alerts
|

Coronary perforation in the drug-eluting stent era: incidence, risk factors, management and outcome: the UK experience

Abstract: Despite treatment of more complex disease, the incidence of coronary perforation has not increased. Major perforations (Ellis class III) are associated with a high rate of emergency coronary artery bypass graft (CABG) and death. Endovascular treatments allow sealing of the perforation in most cases and deaths occur primarily as a result of cardiogenic shock due to occlusion of the culprit artery. Patient risk factors associated with perforation should be considered when planning or performing PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
57
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 19 publications
5
57
2
4
Order By: Relevance
“…This is in line with data from a number of previous studies, 1,3,8,12,13 but there are other reports with a much higher incidence. 2,4,5,7 A possible explanation for the low incidence in the present study is that mainly high-volume centers with a mean annual PCI volume of 1,000 cases participated in the EHS PCI Registry.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This is in line with data from a number of previous studies, 1,3,8,12,13 but there are other reports with a much higher incidence. 2,4,5,7 A possible explanation for the low incidence in the present study is that mainly high-volume centers with a mean annual PCI volume of 1,000 cases participated in the EHS PCI Registry.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast to other analyses, female gender and age were not significant predictors. 2,5 In our analysis, adjunctive antithrombotic therapy did not have an influence on the occurrence of CP. In another study, a higher incidence of CP was observed in patients on glycoprotein IIb/IIIa antagonists.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The largest published series describes 124 events, and the total literature is <1000 cases. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Given the small numbers of events per published series, it has not been possible to examine several key questions relating to the occurrence and outcomes of CP. First, it is unclear from the available evidence what the true incidence of CP is and whether its incidence increasing or decreasing.…”
mentioning
confidence: 99%